(untitled) - McFedries, Paul (Indianapolis, IN, 2008)
Packed with clear, step-by-step screen shots, this visual guide shows you how to tackle more than 130 Windows Home Server tasks. You’ll see how to configure Windows Home Server, connect to computers remotely, add and remove user accounts, use Windows Home Server storage, work with shared folders, restore files from backups, and much more! Helpful sidebars offer practical tips and tricks, and two-page lessons break big topics into bite-sized modules
Keywords: Microsoft Windows server,Operating systems (Computers),Microsoft Windows server,Hệ điều hành (Máy tính)